Robust Biocomposite Film of Polylactic Acid and Ferroferric Oxide as a Radar Absorbing Material - Rafles Sinaga; Wida Banar Kusumaningrum; Yana Taryana; Widya Fatriasari; Zuratul Ain Abdul Hami; Lisman Suryanegara; Holilah Holilah; Yudi Darma (Indonesian Journal of Chemistry, 2023)
The polymer/ferroferric oxide (Fe3O4) foam and aerogel composites generally exhibit superior radar absorptivity performance. However, these composites have poor mechanical and thermal properties. This study manufactured a polylactic acid (PLA)/Fe3O4 bio-composite and evaluated the radar absorptivity, thermal, and mechanical properties of radar-absorbing material. The composites were prepared using a solvent casting method to mix PLA and Fe3O4 at varying concentrations, followed by evaporation, oven drying, and hot pressing into a film. Thermogravimetric analysis showed that the decomposition temperature of the PLA/Fe3O4-5% composite occurred at around 306 °C, which shifted to a lower decomposition temperature of PLA. The addition of 25 wt.% Fe3O4 improved the tensile modulus of neat PLA from 2.92 to 3.55 GPa. The vector network analyzer demonstrated that the addition of Fe3O4 at 25% improved the reflection loss of PLA from –5.17  to -25.83 dB at a thickness of 3 mm, with energy absorbed by 99.74% at frequency position 10.58 GHz. These results demonstrated that PLA/Fe3O4 composites have great potential in radar-absorbing practical applications.